Good Corporate Governance Dalam Mempengaruhi Firm Value dengan Pemoderasi Corporate Social Responsibility - Tjun Tjun Lauw; Joshua Rahadian (Jurnal Akuntansi, 2022)
This study aims to analyze the effect of Good Corporate Governance on Firm Value, with Corporate Social Responsibility (CSR) as a moderating variable. The analytical method used is multiple linear regression. The research sample consisted of 14 companies selected by purposive sampling on basic and chemical industrial companies listed on the Indonesia Stock Exchange for the 2016-2018 period. The results showed that managerial ownership (MOWN), institutional ownership (INST), had no effect on firm value (PBV). While the independent commissioner (KI) has a significant positive effect on PBV. CSR is able to strengthen MOWN, KINST, and KI toward PBV. Keywords: Good Corporate Governance, Firm Value, Corporate Social Responsibility.